2017
DOI: 10.1155/2017/5094608
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology Related to Energy Drinks: A Psychosis Case Report

Abstract: Energy drinks (ED) are nonalcoholic beverages that have caffeine as their most common active substance. The rapid expansion of ED consumption has created concern in the scientific community as well as in the public opinion. We report a psychotic episode probably triggered by ED abuse in a young adult without previous psychotic disorders. We have reviewed the literature regarding the relationship between caffeine, energy drinks, and psychopathology. Few articles have been published about mental health effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
(33 reference statements)
0
10
0
2
Order By: Relevance
“…Single‐patient case studies in adults suggest that ED consumption can precede mental health problems (Hernandez‐Huerta, Martin‐Larregola, Gomez‐Arnau, Correas‐Lauffer, & Dolengevich‐Segal, 2017; Szpak, Allen, Szpak, & Allen, 2012). In contrast, an Italian cross‐sectional study, conducted with children 10–16 years old, found ED intake was associated with regular smoking but not psychological distress (Cofini, Cecilia, Di Giacomo, Binkin, & Di Orio, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Single‐patient case studies in adults suggest that ED consumption can precede mental health problems (Hernandez‐Huerta, Martin‐Larregola, Gomez‐Arnau, Correas‐Lauffer, & Dolengevich‐Segal, 2017; Szpak, Allen, Szpak, & Allen, 2012). In contrast, an Italian cross‐sectional study, conducted with children 10–16 years old, found ED intake was associated with regular smoking but not psychological distress (Cofini, Cecilia, Di Giacomo, Binkin, & Di Orio, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of case reports describe the emergence of psychosis following excessive caffeinated drink consumption in those without previously diagnosed psychotic disorders, with the first clear case being reported in 1936 [8]. More recently, Hernandez-Huerta et al[9], Cruzado et al [10], and Sharma et al [11] have described 3 cases of psychosis arising de novo following excessive caffeine intake. The ages of the 3 patients range from 18 to 32, and daily caffeine intake ranges from 480 mg to 1300 mg per day.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, psychotic symptoms were short lived (with symptoms typically lasting under 1 month) and appeared to be associated with a good prognosis at follow-up (follow-up periods ranged between 6 weeks and 2 years). Intercurrent life stressors (particularly work-related stress) were frequently associated with the high consumption of caffeine/energy drinks in the reported cases of caffeine-associated psychosis [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca; uyuşturucu bağımlılığını hızlandırdığı, epileptik atak ve uyku bozukluklarını tetiklediği, akut psikoz gelişmesine ve hipokalemik paralize neden olduğu da literatürde mevcuttur. 11,21,26,34,35 Enerji içeceğinin majör bileşeni kafein, alkol ve tütün gibi yasal olarak kullanılmaktadır. Ülkemizde Türk Gıda Kodeksi tebliğinde belirlenen düzenlemeler kapsamında, ürün etiketlerinin uyarı başlığı altında kolaylıkla görülebilecek şekilde "Alkol ile karıştırılarak veya beraber tüketilmemelidir.…”
Section: Discussionunclassified
“…Enerji içeceği alımıyla sekonder ilişkisi olduğu düşünülen uzun QT sendromu gelişen hastalar bildirilmiştir. 21 Yapılan araştırmalar, enerji içeceğinin tüketiminin tehlikeli olabileceği ile ilgili üç neden göstermişlerdir; birincisi, başta adölesanlar olmak üzere, düzenli olarak kafein alımının yüksek tansiyon ve uyku bozukluğuna yol açtığıdır. 22 İkincisi, alkol ile birlikte karıştırıldığında alkolün yalnız başına alınmasından daha fazla yan etkileri olduğu gözlenmiştir.…”
unclassified